Pollution Forensic Linguistic Analysis Natalius Pigai’s Good On Social Media - Fatahuddin Burhanuddin; Tajuddin Maknun; Ery Iswary; Firman saleh (Prodi Pendidikan Bahasa Inggris, FKIP, LP3M Universitas Muhammadiyah Sidenreng Rappang, 2022)
This study aims to: (1) explain the meaning of denotation and connotation of defamation on social media, (2) explain the pragmatic analysis (speech acts) of defamation on social media, and (3) explain the juridical effects of defamation on social media. The data in this study are language that contains criminal acts of defamation on social media Facebook. The data source in this study is the social media Facebook. The method used in this research is descriptive qualitative method, data collection techniques in the form of capturing screens, reading techniques, and taking notes. Data were analyzed using qualitative content analysis techniques. The results of this study indicate that: based on the semantic study of NA speech on social media Facebook, NP contains denotative and connotative meanings. The use of the type of animal chosen by the speaker is a different animal from the animals that are used to insult and humiliate. In this pragmatic study of speech is a type of ommissive illocutionary speech act. There is also a metaphorical meaning in the words